THE EFFECT OF INFORMATION GAP TECHNIQUE ON STUDENTS’ SPEAKING ACHIEVEMENT AT THE EIGHTH GRADERS OF SMPN 11 TARAKAN - Sakina, Sakina; Ridwan, Ridwan (Universitas Borneo Tarakan, 2021)
This research aims to find out the effect of using the information Gap technique inimproving student speaking achievement at eighth-grade students of SMP Negeri 11Tarakan. The method used in this research was quasi-experimental. The population ofthis research was 58 students. The researcher used purposive sampling in took asample. In collecting the data, the researcher used a speaking test. Before treatment,the researcher gave Pretest. After that, the researcher gave treatment. After treatment,the researcher gave a posttest. The mean score of each test was compared to know thestudent's improvement in speaking. The mean score of pretests in the experimentalclass was 45.17, and in the control, class was 46.90. The mean score of posttests in theexperimental class was 70.17, and in the control, class was 65.69. The score ofposttests of the experimental class was higher than the control class. The result of theindependent sample t-test showed that the t-test (2.204) higher than the t-table (1.673).It was concluded that the information gap technique has a significant effect on studentspeaking achievement at SMPN 11 Tarakan.